Peptides for diagnosis and treatment of ovarian cancer - Guo, Ling; Wang, Jing; Li, Nana; Cui, Jialin; Su, Yajuan (Frontiers in Oncology, 2023)
Ovarian cancer is the most deadly gynecologic malignancy, and its incidence is gradually increasing. Despite improvements after treatment, the results are unsatisfactory and survival rates are relatively low. Therefore, early diagnosis and effective treatment remain two major challenges. Peptides have received significant attention in the search for new diagnostic and therapeutic approaches. Radiolabeled peptides specifically bind to cancer cell surface receptors for diagnostic purposes, while differential peptides in bodily fluids can also be used as new diagnostic markers. In terms of treatment, peptides can exert cytotoxic effects directly or act as ligands for targeted drug delivery. Peptide-based vaccines are an effective approach for tumor immunotherapy and have achieved clinical benefit. In addition, several advantages of peptides, such as specific targeting, low immunogenicity, ease of synthesis, and high biosafety, make peptides attractive alternative tools for the diagnosis and treatment of cancer, particularly ovarian cancer. In this review, we focus on the recent research progress regarding peptides in the diagnosis and treatment of ovarian cancer, and their potential applications in the clinical setting.